2010
DOI: 10.1253/circj.cj-09-0936
|View full text |Cite
|
Sign up to set email alerts
|

Real World' Comparison of Drug-Eluting Stents vs Bare Metal Stents in the Treatment of Unselected Patients With Acute ST-Segment Elevation Myocardial Infarction

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp rug-eluting stents (DES) have significantly reduced the need for repeat revascularization procedures after percutaneous coronary intervention (PCI) owing to decreased late luminal loss and angiographic restenosis. 1,2 Since their introduction, DES have rapidly substituted bare metal stents (BMS) in the treatment of various coronary artery lesions, including the treatment of ST-segment elevation myocardial infarcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…TYPHOON 20 was also a multicenter, prospectively randomized trial comparing sirolimus-eluting stents (n=355) with BMS (n=357) in primary PCI for STEMI; it demonstrated 1-year ST rates of 3.4% and 3.6%, respectively (P=1.00) in this selected population. Similar findings were reported by Park et al 21 These rates contrast with those from studies excluding STEMI patients and emergency PCI, such Tables 1,2. Tables 1,3.…”
Section: Discussionsupporting
confidence: 86%
“…TYPHOON 20 was also a multicenter, prospectively randomized trial comparing sirolimus-eluting stents (n=355) with BMS (n=357) in primary PCI for STEMI; it demonstrated 1-year ST rates of 3.4% and 3.6%, respectively (P=1.00) in this selected population. Similar findings were reported by Park et al 21 These rates contrast with those from studies excluding STEMI patients and emergency PCI, such Tables 1,2. Tables 1,3.…”
Section: Discussionsupporting
confidence: 86%
“…[19][20][21] In addition to the studies carried out in Western countries, Park et al showed that mid-to long-term outcomes were better in patients receiving DES for AMI in Korea. 22 In a 3-year follow up of the randomized DEDICATION trial, however, the rate of cardiac death was higher in the DES group compared to the BMS group. 23 Most, but not all of these studies have demonstrated the safety and efficacy of DES in patients with AMI.…”
Section: Discussionmentioning
confidence: 94%
“…36-38 However, there is a paucity of reports concerning longer-term prognosis of DES use in ACS. 39 Concerns exist regarding the long-term outcomes of DES vs BMS in patients with ACS in the real-world setting. A high frequency of VLST has been steadily observed in DES-implanted ACS patients.…”
Section: Des Should Be Avoided In Acs Patients Untilmentioning
confidence: 99%